Neutralizing Anti-IL-17A Antibody Demonstrates Preclinical Activity Enhanced by Vinblastine in Langerhans Cell Histiocytosis - Åkefeldt, Selma Olsson; Ismail, Mohamad Bachar; Belot, Alexandre; Salvatore, Giulia; Bissay, Nathalie; Gavhed, Désirée; Aricò, Maurizio; Henter, Jan-Inge; Valentin, Hélène; Delprat, Christine (Frontiers in Oncology, 2022)
Langerhans cell histiocytosis (LCH) is an inflammatory myeloid neoplasm characterised by the accumulation into granulomas of apoptosis-resistant pathological dendritic cells (LCH-DCs). LCH outcome ranges from self-resolving to fatal. Having previously shown that, (i) monocyte-derived DCs (Mo-DCs) from LCH patients differentiate into abnormal and pro-inflammatory IL-17A-producing DCs, and (ii) recombinant IL-17A induces survival and chemoresistance of healthy Mo-DCs, we investigated the link between IL-17A and resistance to apoptosis of LCH-DCs. In LCH granulomas, we uncovered the strong expression of BCL2A1 (alias BFL1), an anti-apoptotic BCL2 family member. In vitro, intracellular IL-17A expression was correlated with BCL2A1 expression and survival of Mo-DCs from LCH patients. Based on the chemotherapeutic drugs routinely used as first or second line LCH therapy, we treated these cells with vinblastine, or cytarabine and cladribine. Our preclinical results indicate that high doses of these drugs decreased the expression of Mcl-1, the main anti-apoptotic BCL2 family member for myeloid cells, and killed Mo-DCs from LCH patients ex vivo, without affecting BCL2A1 expression. Conversely, neutralizing anti-IL-17A antibodies decreased BCL2A1 expression, the downregulation of which lowered the survival rate of Mo-DCs from LCH patients. Interestingly, the in vitro combination of low-dose vinblastine with neutralizing anti-IL-17A antibodies killed Mo-DCs from LCH patients. In conclusion, we show that BCL2A1 expression induced by IL-17A links the inflammatory environment to the unusual pro-survival gene activation in LCH-DCs. Finally, these preclinical data support that targeting both Mcl-1 and BCL2A1 with low-dose vinblastine and anti-IL-17A biotherapy may represent a synergistic combination for managing recurrent or severe forms of LCH.